Addressing childhood obesity in Queensland: Aboriginal and Torres Strait Islander Health Worker perspectives and practices. (17th March 2022) - Vincze, Lisa; Boswell, Megan; Atkins, Heidi; Littlewood, Robyn; Williams, Lauren
Abstract: Issue Addressed: Obesity disproportionately impacts Aboriginal and Torres Strait Islander children compared to non‐Indigenous children. Aboriginal and Torres Strait Islander Health Workers (AHWs) in Queensland support the health of Aboriginal and Torres Strait Islander peoples. However, little is known about their perspectives and practices on addressing childhood obesity. The aim of this study was to investigate AHW perspectives and clinical practice behaviours with Aboriginal and Torres Strait Islander children and their families. Methods: In a cross‐sectional mixed‐methods approach, a purpose‐developed online survey (25 items) was distributed to the AHW workforce in Queensland ( 100 AHWs). The survey explored [1] role characteristics, [2] current attitudes and beliefs about childhood obesity, [3] barriers to discussing weight management, [4] clinical practice behaviours and [5] demographic characteristics. Eight AHWs responding to the survey also participated in semi‐structured telephone interviews to discuss their survey responses. Results: Fifty‐five AHWs responded and 45 completed the survey. While the majority of respondents (91%) agreed that addressing childhood obesity was an important part of their role, fewer (67%) agreed that obesity was an issue in Aboriginal and Torres Strait Islander peoples. Over half (55%) found it difficult to discuss overweight and obesity with children and families and only 22.5% reported measuring height and weight often. Key themes included a willingness to address childhood obesity, with experience and training being key enablers to discussing the issue. There was a perceived lack of culturally appropriate programs to support AHWs working with families. Conclusions: AHWs report a willingness to address childhood obesity within their roles, however many find it difficult to raise the issue with families, with even fewer routinely undertaking obesity assessment practices. So what?: These findings could inform training initiatives for AHWs to optimise screening, identification, referral, and treatment of childhood obesity in Aboriginal and Torres Strait Islander communities.